Locke and Muller on Language, Thought and Religion - Sztajer, Sławomir (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
This article is a contribution to research on the influence of John Locke’s philosophy on Friedrich Max Müller’s science of language, thought and religion. In the present study, influence is understood not merely as a more or less original continuation of Locke’s philosophy, but also as an opposition to his achievements and criticism of his thought. While in the former case Locke’s achievements form the basis for philosophical considerations, in the latter they constitute a negative point of reference which determines, to a considerable degree, debates on philosophical issues. The author of this article argues that many hypotheses elaborated by Müller, especially in the fields of the science of language and the science of religion, are based on Locke’s philosophical achievements. Among the theories developed by Müller are the conception of mythology as a “disease” of language, the theory of metaphor as a linguistic phenomenon that allows language users to represent those domains of discourse which transcend sense experience, and a study concerning the relation between language and thought.